Effect of mastitis on milk quality of Friesian cows in a Khartoum state - Mohamed, Ibtisam Elyas; Owni, Osman Ali Osman El; Mohamed, Galal Eldeen Elazahri (The Indian Journal of Animal Sciences, 2012)
Milk samples from clinically-infected, subclinically-infected and healthy cows (15 samples each) were evaluated for total bacterial counts, titratable acidity, total solids and ash. Log. total bacterial counts and ash content increased with the intensity of infection, while the total solids and titratable acidity decreased with intensity of the disease. The mean differences were significant for log. bacterial counts in subclinical and clinical mastitic milk (P